Increased type I collagen degradation correlates with disease severity in rheumatoid arthritis. Issue 12 (December 1993) - Hakala, M; Risteli, L; Manelius, J; Nieminen, P; Risteli, J
Abstract : OBJECTIVES--To assess the extent and clinical significance of type I collagen degradation in rheumatoid arthritis (RA). METHODS--Serum samples from 90 consecutive patients with RA from a cross-sectional population based study and 90 age- and sex-matched controls were analysed with the new assay of cross-linked carboxyterminal telopeptide of type I collagen (ICTP). RESULTS--Patients with RA had significantly higher concentrations of ICTP than the controls. ICTP correlated strongly with measures of impairment in RA, such as the erosive state of joint disease (ES) (r = 0.57, p < 0.001) and Keitel function test (KFT) (r = 0.49, p < 0.001), and more weakly with various disease activity markers. When erythrocyte sedimentation rate (ESR), ES or KFT were used as indicators of disease severity among the patients with disease duration over five years, ICTP distinguished the more serious RA from milder cases. CONCLUSIONS--Elevated serum concentrations of ICTP are common in RA and are associated with signs of aggressive disease.